A Short Review on Enterococcus faecalis: Short Review: Short Review on Enterococcus faecalis (Biological Sciences - PJSIR, 2024)
The gastrointestinal tract gets colonized during the first two years of life and after this period, gut microbiota either stabilize or fluctuate throughout life. Enterococcus faecalis is one of the species found in gut and is responsible for various infections and colorectal cancer. Bacterium E. faecalis can easily be diagnosed in the laboratory, as it is gram-positive, present in pairs and short chains. Antimicrobial therapy can be used to treat enterococcal infections but its excessive use has led to the emergence of vancomycin-resistant Enterococcus. Enterococcal infections are usually nosocomial and can be reduced by taking preventive measures. The purpose of this study is to review all the aspects of E. faecalis, to create awareness to control Enterococcal infections and to promote the discovery of new drugs against the resistant faecalis.